ANALISIS KINERJA PETUGAS TERMINAL INSPECTION SERVIVE (TIS) TERHADAP STANDAR OPERATIONAL PROCEDURE (SOP) DI TERMINAL BANDAR UDARA RAHADI OESMAN KETAPANG - Danang Indrawan; Aditya Dewantari (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to determine the monitoring system for Terminal Inspection Service (TIS) facilities at Rahadi Oesman Airport, Ketapang, to determine the performance of Terminal Inspection Service (TIS) officers against the Standard Operational Procedure (SOP) at Rahadi Oesman Airport, Ketapang. This research was conducted at Rahadi Oesman Airport Terminal Ketapang covering data obtained from company documents through interviews. The method used in this study uses qualitative methods and data analysis techniques as follows: Data reduction, data presentation, and data verification. The facility supervision system at Rahadi Oesman Airport Ketapang is carried out routinely by Terminal inspection service (TIS) officers and the results of the report are submitted to the head of Rahadi Oesman Airport for policy making and follow-up. The performance of the Terminal Inspection Service (TIS) officers is in accordance with the Standard Operational Procedure (SOP) as evidenced by the suitability of the performance carried out and strengthened by the results of the officer's report.